Is bigger better? The impact of the size of banks on credit ratings - Patrycja Chodnicka-Jaworska (Financial Internet Quarterly, 2020)
The aim of the paper was to analyse the factors influencing European banks' credit ratings by taking into account the size of these institutions. A literature review onthe indicators that can impact bank notes has been made. As a result, the following hypotheses have beendrawn:banks' capital adequacy, profitability, liquidity and management quality have a significant influence on bank credit ratings. Bigger banks receive higher credit ratings than the smaller ones in similar financial conditions. To verify the presented hypotheses ordered logit panel data models have been used. The analysis has been prepared by using the quarterly data from the Thomson Reuters database for the period between 1998 to 2015. The European banks' long-term issuer credit ratings proposed by S&P, Fitch and Moody are used as dependent variables. The sample has been divided into subsamples according to the size of a bank and banking sector and capitalization.
Keywords: C23; G21; G24; 330; credit rating; logit panel data models; banking sector